A 'Primitive' Latin America on View at the 1889 Exposition Universelle. (1st June 2014) - Jiménez, Maya
At the Exposition Universelle in Paris (1889), Mexico's national pavilion was designed in the Aztec revival style and stood alongside a reconstruction of an Aztec village. These structures, as well as the artworks exhibited within their walls, perpetuated a view of a primitive and unchanged Mexico. Conversely, Venezuelan Arturo Michelena garnered an award for his painting of a French Royalist heroine, and Argentine Eduardo Schiaffino for his depiction of a nude, demonstrating the appeal of European and Classical subjects among exhibition critics. How did these divergent views of Latin America function on the international stage, and particularly at universal expositions? This article seeks to explore the ways through which Latin American countries either addressed or shunned their pre-Hispanic past at the Exposition Universelle, revealing the ways in which their pavilions, artifacts and fine art catered to notions of the 'primitive' as much as it did subvert them.